The Potential Role of Salivary NT-proBNP in Heart Failure - Aidonis Rammos; Aris Bechlioulis; Petros Kalogeras; Chris J. Watson; Pietro Salvo; Tommaso Lomonaco; Olga Kardakari; Evanthia E. Tripoliti; Yorgos Goletsis; Dimitris I. Fotiadis; Christos S. Katsouras; Lampros K. Michalis; et al. (Life, 2023)
Background: Serum natriuretic peptides (NPs) have an established role in heart failure (HF) diagnosis. Saliva NT-proBNP that may be easily acquired has been studied little. Methods: Ninety-nine subjects were enrolled; thirty-six obese or hypertensive with dyspnoea but no echocardiographic HF findings or raised NPs served as controls, thirteen chronic HF (CHF) patients and fifty patients with acute decompensated HF (ADHF) requiring hospital admission. Electrocardiogram, echocardiogram, 6 min walking distance (6MWD), blood and saliva samples, were acquired in all participants. Results: Serum NT-proBNP ranged from 60–9000 pg/mL and saliva NT-proBNP from 0.64–93.32 pg/mL. Serum NT-proBNP was significantly higher in ADHF compared to CHF (p = 0.007) and in CHF compared to controls (p < 0.05). There was no significant difference in saliva values between ADHF and CHF, or between CHF and controls. Saliva and serum levels were positively associated only in ADHF patients (R = 0.352, p = 0.012). Serum NT-proBNP was positively associated with NYHA class (R = 0.506, p < 0.001) and inversely with 6MWD (R = −0.401, p = 0.004) in ADHF. Saliva NT-proBNP only correlated with age in ADHF patients. Conclusions: In the current study, saliva NT-proBNP correlated with serum values in ADHF patients, but could not discriminate between HF and other causes of dyspnoea. Further research is needed to explore the value of saliva NT-proBNP.